THE INFLUENCE OF INFANT MASSAGE ON WEIGHT GAIN IN BABIES AGED 1-6 MONTHS - Andi Herawati; Farida Hariyani; Novi Pasiriani (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Massage is the oldest method of treatment in the world. Massage encompasses both healthcare and therapy. There are many benefits obtained from performing infant massage, one of which is the improvement of infant weight gain. One of the issues concerning the growth and development of toddlers in Kutaikartanegara, East Kalimantan, is the prevalence of underweight toddlers at 17.5% and wasted toddlers at 9.0%. The aim of this study is to analyze the influence of infant massage classes on infant weight gain. The research design is a quasi-experiment with a Two Group Pretest Posttest design. The research subjects are divided into two groups: the control group and the treatment group, and both pretest and posttest measurements are conducted. Based on the results of the t-test using paired t-test analysis, the significance value is p=0.000 (p<0.05). This indicates that there is an influence of infant massage classes for infants aged 1-6 months on weight gain. The average increase in infant weight after the intervention is 5200 grams. There is an influence of infant massage on infant weight gain at PMB Andi Herawati in the year 2023.